Visionary leadership and achievement motivation as predictors of teacher creativity: An empirical inquiry - Esisuarni, Esisuarni; Anisah, Anisah; Rusdinal, Rusdinal; Al Kadri , Hanif (Universitas Jambi, Indonesia, 2026)
This study investigates the impact of the principal's visionary leadership and achievement motivation on teacher creativity. The study employed quantitative correlational design, with a population of 684 civil servant teachers from public middle schools in Agam Regency. Using the Cochran formula with a 10% margin of error, the stratified proportional random sampling method selected a sample of 176 teachers. Data were collected through a validated and reliable Likert-scale questionnaire. The data were analyzed using SPSS version 26, including normality, linearity, multicollinearity, regression significance, and correlation tests. The results reveal that both the principal's visionary leadership and achievement motivation significantly enhance teacher creativity. These findings highlight the importance of improving both leadership and motivation to foster teacher creativity through targeted interventions.